Parents' role in cultural socialisation of ethnic groups in Malaysia - Ting, Su Hie (2018)
Among the agents of cultural socialisation, parents play an important role in identity formation. Positive aspects of the cultural socialisation in terms of cultural heritage and pride are often studied, but the negative aspects are relatively unexplored by researchers. 'This study examined Ihe parents' role in cultural socialisation of ethnic groups in Malaysia. The specific aspects studied were cultural socialisation, preparation for bias, and promotion mistrust. A survey was conducted among 272 students in a university. The results showed that the students reported relatively higher frequency of socially acceptable aspects of cultural socialisation than "negative aspects". The reported frequency of cultural socialisation into pluralism is relatively higher, in that the parents had talked to them about pride in their cultural heritage and appreciation of other ethnic groups up to two times that )'ear. This is expect.ed because "unity in diversity" is the mainstay of harmonious ethnic relations in a pluml society, and parents need to inculcate these values ill their children. The study showed that the parents' role in cultural socialisation had decreased by the time the students were in university.